Obesity in Patient with Grown Up Congenital Heart Disease Ventricular Septal Defect with Pulmonary Hypertension in Sanglah Hospital, Bali, Indonesia - Nabila Natasya; Maya Paramita Wijaya; Yosi Kusuma; I Made Putra Swi Antara (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Ventricular septal defect (VSD) is a congenital heart disease (CHD) which characterized bya hole in the wall that separate between the right and left ventricle. There are several typesof VSD based on its location, which are perimembranous/conoventricular, subpulmonary/conotruncal, supracristal/doubly commited, muscular and atrioventricular canal/inlet. AVSD is one of the most common CHD which occurs in approximately 2-6 of every 1,000live births and accounts for more than 20% of all CHDs. However, the population of VSDpatients with grown up congenital heart disease (GUCH) is still uncertain. We are presentinga rare case of a 19 year old patient with congestive heart failure NYHA functional class IVdue to uncorrected left-to-right shunt supracristal VSD with body mass index of 35.5 kg/m2. He presented in the emergency room with acute decompensated heart failure profileB. Echocardiography revealed decreased left ventricle (LV) systolic function, normal rightventricle (RV) systolic function, decreased LV diastolic function, and dilated left atriumand LV. We plan to perform right heart catheterisation and pulmonary artery oxygenresponsiveness test followed by VSD closure in this patient. Another explanation will bediscussed in this paper.